Barbados : 2010 Article IV Consultation-Selected Issues. (IMF Staff Country Reports; Country Report, 2010)
The short-term recovery of the Barbados economy will critically depend on the rebound of demand for its services in its traditional markets. As a small tourist-dependent economy with a fixed exchange rate and volatile capital inflows, Barbados could shore up its external sector through fiscal consolidation and structural reforms to raise sustainable growth rates. Barbados's financial system appears to have been broadly resilient up to now; preserving its soundness in an environment weakened by the recession requires strengthening the regulatory and supervisory framework.